Blood Donor Counseling Services at Blood Center of Indonesian Red Cross, Semarang City: In-person Counseling Method Implementation and Online Counseling Design - Yuli Arinta Dewi; Maria Rika Jawan; Jessica Christanti (Nur Science Institute, 2022)
The blood center has to managed blood donors through blood donor counseling. Covid-19 has impacted blood donor services, including in-person blood donor counseling services. This study aimed to analyze the implementation of in-person blood donor counseling in the Blood Center of the Indonesian Red Cross, Semarang City, and design the online blood donor counseling. This descriptive study uses a mixed method. In qualitative methods, primary data was obtained from observations, interviews, and focus group discussions. the secondary data is obtained by searching documents. The result of this study was in-person blood donor counseling at the Blood Center of the Indonesian Red Cross, Semarang City maintained individual approach between the counselors and the clients. The successful implementation of in-person blood donor counseling was 50% of the total calls during pandemic. The obstacles faced by the blood center during the COVID-19 pandemic was conducting in-person blood donor counseling thus the online blood donor counseling design warranted. Online blood donor counseling was developed using communication technology based on an android system with chatting services using a mobile phone and the internet.